Allies in Arms: Turkish-American Defense Relations - Kanat, Kilic Bugra. author. aut Link
XIII, 255 p. 1 illus.
Keywords: “Allies in Arms: Turkish-American Defense Relations” offers an examination of the strategic evolution of military cooperation between the United States and Turkey, with a particular focus on the aerospace and defense industry. The book serves as an introductory resource for readers interested in the changing contours of the US-Turkey bilateral relationship. It outlines the early cooperation, moments of strain, and Turkey’s drive for greater defense self-sufficiency. It illustrates how US military assistance advanced Turkey’s defense capabilities while creating strategic dependence and vulnerability. The book traces this dynamic through key events, including the 1960s Cyprus crisis, the 1970s US arms embargo, Turkey’s F-16 industrial partnership, its involvement in the F-35 program, and the acquisition of the Russian S-400 system. It moves beyond historical narrative to assess the current and future international defense ties. In proposing solutions, it calls for a revised bilateral framework that reflects Turkey’s growing influence. Kılıç Buğra Kanat is Associate professor of Political Science at Penn State Erie, The Behrend College, USA. He is also the Research Director at the SETA Foundation, Washington. He was awarded the Outstanding Research Award and Council of Fellows Faculty Research Award at Penn State Behrend. Dr. Kanat’s writings have appeared in Foreign Policy, Insight Turkey, The Diplomat, Middle East Policy, Arab Studies Quarterly, Mediterranean Quarterly, Journal of South Asian and Middle Eastern Studies, Journal of Balkan and Near Eastern Studies, and Journal of Muslim Minority Affairs. He is the author of A Tale of Four Augusts: Obama’s Syria Policy, Vulnerable Partnership: The History of US-Turkey Strategic Relations and Mapping the Fault Lines in Turkey-US Relations: Making the Vulnerable Partnership. Ozan Ahmet Çetin is an Assistant Professor at the Turkish National Defense University. He earned his PhD from American University’s School of International Service, where he specialized in technologies with national security implications. He also holds an MA in War Studies from King’s College London and a BA in Political Science and International Relations from Boğaziçi University. Çetin’s research interests include international security, emerging technologies, defense policy, artificial intelligence, and cybersecurity.